Guidelines on management of low-grade gliomas: report of an EFNS-EANO* Task Force - Soffietti, Riccardo; Baumert, B.G.; Bello, L.; Deimling, Andreas von; Duffau, H.; Frénay, M.; Grisold, W.; Grant, R.; Graus, F.; Hoang-Xuan, K.; Klein, M.; Melin, B.; et al. (European journal of neurology, 2010)
Background: Diffuse infiltrative low-grade gliomas of the cerebral hemispheres in the adult are a group of tumors with distinct clinical, histological and molecular characteristics, and there are still controversies in management. Methods: The scientific evidence of papers collected from the literature was evaluated and graded according to EFNS guidelines, and recommendations were given accordingly. Results and conclusions: WHO classification recognizes grade II astrocytomas, oligodendrogliomas and oligoastrocytomas. Conventional MRI is used for differential diagnosis, guiding surgery, planning radiotherapy and monitoring treatment response. Advanced imaging techniques can increase the diagnostic accuracy. Younger age, normal neurological examination, oligodendroglial histology and 1p loss are favorable prognostic factors. Prophylactic antiepileptic drugs are not useful, whilst there is no evidence that one drug is better than the others. Total/near total resection can improve seizure control, progression-free and overall survival, whilst reducing the risk of malignant transformation. Early post-operative radiotherapy improves progression-free but not overall survival. Low doses of radiation are as effective as high doses and better tolerated. Modern radiotherapy techniques reduce the risk of late cognitive deficits. Chemotherapy can be useful both at recurrence after radiotherapy and as initial treatment after surgery to delay the risk of late neurotoxicity from large-field radiotherapy. Neurocognitive deficits are frequent and can be caused by the tumor itself, tumor-related epilepsy, treatments and psychological distress.